Predictors of Academic Achievement among Physical Education and Sports Undergraduate Students - Ertuğrul Şahin; Resul Çekin; İlknur Yazıcılar Özçelik (MDPI AG, 2018)
Although a number of studies have attempted to determine the antecedents, correlates, and consequences of students' academic performance, there are few studies in the literature that examine the correlates of academic achievement for physical education and sports undergraduate students. The aim of this study was to investigate the relationship between the academic achievement of first-year physical education and sports students and their sociodemographics, attitudes towards the teaching profession, personality traits, and achievement goal orientations. The participants of the study consisted of 127 (67% male) physical education and sports students, ranging in age from 16 to 30 years old when they began their studies. Participants responded to a questionnaire to determine their sociodemographic characteristics, their attitudes towards the teaching profession in their high school years, their core self-evaluations, and their achievement goal orientations. Pearson correlation analysis results showed that students' first year grade-point average (GPA) was associated with gender, high school GPA, core-self evaluations, and mastery-approach achievement goal orientation. Results of the regression analysis suggested that the three variables that predicted the students' first year GPA were their mastery-approach scores, attitudes towards the teaching profession in high school years, and high school GPA. In order to prevent academic failure in physical education and sports students, those who do not have a mastery-approach goal orientation and who had a low high school GPA should be identified at the beginning of the academic year, so that educational interventions can be directed at these students.